Arquitetura de contêiner: uma alternativa para a habitação social - Castro, Lara Lima (2019)
Taking as a starting point the history of Social Interest Housing and its current situation in a global context, this paper concludes the course on the use of the container in archi- tecture as a possibility to contribute to this social problem, considering its advantages and disadvantages as a technique constructive Bibliographical researches were carried out, studies on environmental comfort were carried out due to the characteristics of the mate- rial, container identification as a sustainable element, construction process of a container building and costing. It also addresses the Itaqui Port present in São Luís, Maranhão. The idea of this work is to analyze the insertion of this material in popular housing.